USER REVOCATION WITH PUBLIC AUDITING FOR SECURE CLOUD DATA SHARING - M. Anandakumar; J. Israelin Insulata; S. Dilipkumar (International Journal of Innovations in Engineering Research and Technology, 2021)
Cloud storage auditing refers to the verification of exactness of shared data in cloud. Different users from different groups share different data in cloud. Privacy protection becomes the biggest question mark in cloud’s data services. To ensure perfection of the cloud data and for efficient user revocation, Third Party Auditing is to be done with novel Collusion Resistant Proxy Re-signature Scheme. When a user gets revocated, the cloud is much able to resign the data chunks; these data chunks were already acknowledged by the repudiated user. But, now the cloud re-stamps with a re-signing key, and this process enhances the potency of the system. Moreover, Auditing has to be done over shared data which heightens the reliability of cloud data.